Formative Period Obsidian Exchange along the Pacific Coast of Mesoamerica. (27th March 2014) - Ebert, C. E.; Dennison, M.; Hirth, K. G.; McClure, S. B.; Kennett, D. J.
Abstract : Long‐distance networks for the transport of exotic goods and the beginnings of specialized craft production first appear in Mesoamerica during the Formative Period. The results of portable X‐ray fluorescence (pXRF) analysis of 456 obsidian artefacts imported to the Pacific coast site of La Zanja (Guerrero, Mexico) indicate that long‐distance exchange of finished obsidian blades along the coast began during the Early Formative ( c .1400–1000 calbc ) and remained constant into the Middle Formative Period ( c .800–550 calbc ). Comparisons with sourcing studies from elsewhere in Mesoamerica indicate the development of a major Pacific coast trade network during the Formative Period that linked coastal Guerrero to the central Mexican highlands and the Valley of Oaxaca. Weaker connections existed with Gulf coast obsidian trade networks that traversed the Isthmus of Tehuantepec. As the first obsidian sourcing study from coastal Guerrero, these data contribute to a greater understanding of the development of exchange networks in Mesoamerica during the Formative Period.